CPAP improves sleep stability and attenuates acute nocturnal hypertension (NBPF) in OSA, with maximal benefits in severe cases - Liangcai Yu; Lan Shu; Simin Gao; Lin Li (Frontiers in Neurology, 2025)
ObjectiveTo investigate the effects of continuous positive airway pressure (CPAP) therapy on sleep architecture, particularly the microarousal index (MAI), and the frequency of nocturnal acute blood pressure surge events (NBPF) in patients with obstructive sleep apnea (OSA), and to analyze the association between improvements in sleep architecture (especially reduced MAI) and decreased NBPF.MethodsA retrospective analysis was conducted on 477 patients diagnosed with OSA at the Sleep Medicine Center of West China Fourth Hospital, Sichuan University, between January 2021 and January 2023, who received CPAP therapy (mean age 42.70 ± 10.90 years; mild: 92, moderate: 108, severe: 277). Comparisons were made of polysomnography (PSG)-monitored sleep architecture parameters (N1%, N2%, N3%, R%, MAI) and nocturnal blood pressure indices (SBP, DBP, NBPF) before and after CPAP treatment. NBPF was defined as the number of events per hour where nocturnal systolic blood pressure (SBP) increased by >12 mmHg.Results(1) Baseline characteristics: N1%, N2%, SBP, DBP, and NBPF significantly increased, while R% and N3% significantly decreased with increasing severity of OSA (p < 0.05). (2) Overall efficacy: After CPAP treatment, N1% significantly decreased, N3% significantly increased, and DBP and NBPF significantly decreased (p < 0.05). (3) Subgroup analysis: All patients experienced significant reductions in MAI, N1%, N2%, and NBPF, and significant increases in R% after CPAP treatment (p < 0.05); N3% significantly increased in moderate and severe patients (p < 0.05); SBP and DBP improvements were most significant in severe patients (p < 0.05). (4) Correlation and linear regression analysis: NBPF was significantly correlated with sleep structure parameters, showing an independent positive correlation with MAI (β = 0.375, p < 0.001) and an independent negative correlation with N3% (β = −0.143, p = 0.001).ConclusionThe first night of positive airway pressure (PAP) therapy significantly improves sleep architecture and effectively reduces nocturnal blood pressure while suppressing acute systolic blood pressure (NBPF) elevations in OSA patients, especially those with severe disease.